The family Bignoniaceae in Tunisia, first survey including new floristic records to North Africa with nomenclatural notes - El Mokni, Ridha; Iamonico, Duilio (Hacquetia, 2024)
Botanical surveys carried out during the last 13 years throughout central and northern Tunisia (North Africa) allow to find first national and continental N-African records of non-native taxa belonging to Bignoniaceae. The genera Catalpa, Podranea, and Tecomaria are new for N-Africa (Catalpa is new for the whole Africa). Tecomaria capensis is here considered as a naturalized alien species, whereas Campsis radicans, Catalpa bignonioides, Jacaranda mimosifolia, Podranea brycei, P. ricasoliana, and Tecoma stans are casuals. Distribution in Tunisia, phenology, and original photographs are provided for each species. A diagnostic key for Tunisian Bignoniaceae is also given. Moreover, the name Tecoma ricasoliana (basionym of Podranea ricasoliana) is lectotypified on a specimen preserved at FI (isolectotypes at FI and K), whereas the holotype indication of the name Bignonia capensis (basionym of Tecomaria capensis), made in Flora of Tropical East Africa, is here corrected according to the Art. 9.10 of Shenzhen Code (lectotype at UPS; isolectotype, here reported for the first time, at LD).